Alpha-Chymotrypsin Protects Against Acute Lung, Kidney, and Liver Injuries and Increases Survival in CLP-Induced Sepsis in Rats Through Inhibition of TLR4/NF-κB Pathway - Senousy SR; Ahmed ASF; Abdelhafeez DA; Khalifa MMA; Abourehab MAS; El-Daly M (Dove Medical Press, 2022)
Shaymaa Ramzy Senousy,1 Al-Shaimaa F Ahmed,1 Dalia A Abdelhafeez,2 Mohamed Montaser A Khalifa,1 Mohammed AS Abourehab,3 Mahmoud El-Daly1 1Department of Pharmacology and Toxicology, Faculty of Pharmacy, Minia University, Minia, 61519, Egypt; 2Department of Pathology, Faculty of Medicine, Minia University, Minia, Egypt; 3Department of Pharmaceutics, Faculty of Pharmacy, Umm Al-Qura University, Makkah, 21955, Saudi ArabiaCorrespondence: Al-Shaimaa F Ahmed, Department of Pharmacology and Toxicology, Faculty of Pharmacy, Minia University, Minia, Egypt, Tel +20 1020018842, Email shaimaa.faissal@minia.edu.egAbstract: Inflammation and oxidative stress play a major role in the development of sepsis and its associated complications, leading to multiple organ failure and death. The lungs, liver, and kidneys are among the early affected organs correlated with mortality in sepsis. Alpha-chymotrypsin (α-ch) is a serine protease that exerts anti-inflammatory, anti-edematous, and anti-oxidant properties.Purpose: This study was undertaken to elucidate if the anti-inflammatory and anti-oxidant effects of α-ch observed in previous studies can alleviate lung, liver, and kidney injuries in a cecal ligation and puncture (CLP)-induced sepsis model, and thus decrease mortality.Materials and Methods: Septic animals were given α-ch 2 h post CLP procedure. Sepsis outcomes were assessed in the lungs, liver, and kidneys. Separate animal groups were investigated for a survival study.Results: CLP resulted in 0% survival, while α-chymotrypsin post-treatment led to 50% survival at the end of the study. Administration of α-chymotrypsin resulted in a significant attenuation of sepsis-induced elevated malonaldehyde (MDA) and total nitrite/nitrate (NOx) levels. In addition, there was a significant increase in reduced glutathione (GSH) content and superoxide dismutase (SOD) activity in the lungs, liver, and kidneys. Administration of α-ch reduced elevated tissue expression of toll-like receptor-4 (TLR4), nuclear factor kappa-B (NF-κB), myeloperoxidase (MPO), and inducible nitric oxide synthase (iNOS). Alpha-chymotrypsin resulted in a significant reduction in serum levels of tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6). Alpha-chymotrypsin attenuated the rise in serum creatinine, cystatin C, blood urea nitrogen (BUN), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels that was observed in the septic group. In addition, α-ch significantly reduced the lung wet/dry weight ratio, total protein content, and leukocytic counts in bronchoalveolar lavage fluid (BALF). Histopathological examination of the lungs, liver, and kidneys confirmed the protective effects of α-ch on those organs.Conclusion: α-ch has protective potential against sepsis through lowering tissue expression of TLR4, NF-κB, MPO, and iNOS leading to decreased oxidative stress and inflammatory signals induced by sepsis. This effect appeared to alleviate the damage to the lungs, liver, and kidneys and increase survival in rats subjected to sepsis.Keywords: Sepsis, CLP, TNF-α, Cytokines, ROS, TLR-4, iNOS